Pengaruh Kepercayaan Merek, Kualitas dan Harga terhadap Keputusan Pembelian Produk Face Wash Wardah Kel. Babura Medan Sunggal - Nainggolan, Gloria Angelina Vanessa; Tarigan, Eka Dewi Setia (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study analyzes the influence of brand trust, product quality, and price on the purchasing decision of Wardah Face Wash in Babura Sub-district, Medan Sunggal. The research is based on the low Top Brand Index of the product (6.90%), despite Wardah being a leading local brand. Using a quantitative approach and 100 respondents, the data were analyzed through multiple linear regression. The results show that brand trust and product quality have a significant partial effect on purchasing decisions, while price does not. Simultaneously, all three variables have a significant effect, contributing 27.8% to purchasing decisions. The study recommends that Wardah strengthen its brand trust and product quality as key strategies, particularly in Muslim-majority urban areas like Medan Sunggal.